Online Footprint Imitation of a Humanoid Robot by Walking Motion Parameterization - Kim, Sung-Kyun; Hong, Seokmin; Kim, Doik; Oh, Yonghwan; You, Bum-Jae; Oh, Sang-Rok (IEEE/RSJ 2010 INTERNATIONAL CONFERENCE ON INTELLIGENT ROBOTS AND SYSTEMS (IROS 2010), 2010)
There are many difficulties in operating a humanoid which has high degree-of-freedom and instability in balancing its body. In addition, due to the shape of a humanoid, it is expected to have motions like a human. In order to overcome its operational difficulties and to provide a human-like motion, a teleoperation with the motion imitation is studied in this paper. Specifically, a framework for online generation of a footprint from a human walking motion is proposed. The human walking motions acquired from a motion capture device are parameterized and normalized to give a human independent foot motion. The normalized parameters are restored by a humanoid considering its hardware limit. The restored footprints generate a walking trajectory of a humanoid, which imitates the human walking motion in terms of the footprint. Experiments are conducted with MAHRU-R, a humanoid robot developed in KIST.